Comparison of remote sensing techniques in mapping hydrothermal alteration associated with Ovacik epithermal gold-silver mineralization - C. Kwang; H. Uygucgil (The Southern African Institute of Mining and Metallurgy, 2025)
The use of remote sensing and geographic information system techniques in mineral exploration is still underutilised. There is a need to explore the potential of new robust remote sensing and geographic information system techniques in the field of mineral exploration. In this study, we mapped the argillic alteration associated with epithermal gold-silver mineralisation. A band ratio of band5/band6 and Crósta technique on Advanced Spaceborne Thermal Emission and Reflection Radiometer within the Google Earth Engine Environment was applied. The bands 5 and 6 were selected for the band ratio after critically analysing and comparing the illite spectral extracted from the Advanced Spaceborne Thermal Emission and Reflection Radiometer image and the illite spectral obtained from the United States Geological Survey spectral library. The band ratio and Crósta technique identified and mapped the Ovacik goldmine and other argillic alteration zones. Even though both methods mapped out the argillic alteration zones associated with gold-silver mineralisation, the Crósta technique produced the optimal argillic alteration. The study demonstrates the analytical capabilities of Google Earth Engine in image processing and analysis for mineral exploration, such as discovering hydrothermal alteration associated with mineralisation.